Fertility transition in India: An application of Bongaarts model - Aparna Aparajita Dash; DA Nagdeve (Global Journal of Fertility and Research - Peertechz Publications, 2020)
Fertility in India has been steadily declining. It almost reached the replacement level in 2015 to 2016 and evidence shows that proximate determinants has a direct influence on fertility. The study aims at calculating the proximate determinants of fertility in India for the period from 2005 to 06 and 2015 to 16 as well as determine the most significant proximate determinant of fertility in India. It also examines the rural - urban fertility differentials for the year 2015 to 2016. The proximate determinants of fertility for few selected states in India has been calculated from 2015 to 2016. The study of the proximate determinants can help expanding clinical and community based contraceptive distribution, promoting breastfeeding, increasing age at marriage and reduce unintended pregnancies. The study is based on data obtained from National Family and Health Survey Round 3 and National Family and Health Survey Round 4. Bivariate analysis had been done to analyze the distribution of currently married women at age of 15 to 49 by biological and behavioral characteristics as well as decomposition analysis had been used to find the contribution of each indices. It is revealed from the study that an increase in use of contraception has led to decline in Total Fertility Rate (TFR) over the decade. The knowledge of contraception is almost universal in India. Even after a slight decline in proportion married, there had been a considerably high contribution of the proportion married towards increasing Total Fertility Rate (TFR). It is evident from the decomposition that only the increase in use of contraception has a positive impact on declining fertility.